Pemasangan Jaringan Internet Berbasis WiFi Untuk Meningkatkan Akses Komunikasi Warga Di Desa Durian - Rahman Ahyar Rosidi; Muhammad fauzi Zulkarnaen; Wahyu Hadi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Durian Village is a village located in Janapria District, Central Lombok Regency. Currently, there is an internet network available in Durian Village, but the speed and quality of the internet network in several places is not good. The condition of infrastructure in Durian Village is still very poor, especially internet access is still very limited, while communication needs are increasing. The aim of this community service program is to install a WiFi-based internet network to improve communication access for residents and the use of information and communication technology (ICT) for the people of Durian Village, Janapria District. Internet installation begins with preparing the device and planning the location of the device so that the signal coverage can be wider. Installation of internet network infrastructure where needed and wider coverage for residents. The implementation of the internet installation was also assisted by STMIK Lombok students. After installing the internet network, the internet network signal area is tested. Internet network testing is carried out by testing signal strength and internet speed which is found to be sufficient to meet internet access standards for communication access and running streaming media applications.